An Analysis of Students' Errors to Find the Result Reflection in Coordinate Plane Based On in the Newman Error Analysis Nints-Grade Students of Junior High School 2 Sampit - Ayu Amelia Sari; Dwi Priyo Utomo; Zukhrufururrohmah Zukhrufururrohmah (Department of Mathematics Education University of Muhammadiyah Malang, 2019)
This study aimed to determine the types and the causes of students' errors in finding the results of reflection in the field of coordinates based on the Newman problem-solving. This research used descriptive research with a quantitative approach. The data collection techniques were written test and a structured interview with the research subjects were Nints-grade students of Junior High School 2 Sampit. Based on the results of the data analysis, there were errors made by students, namely: (1) there were no mistakes in the problem of reading stage, (2) students were not able to write down the known and asked even though students understood the questions presented in the stage of understanding the problem, (3) did not change the questions into a coordinate field in the stage of transformation problem, (4) misplaced of the result reflection and miscalculating the result of reflection on the process skill stage, (5) did not writing down the answers or conclusions in the writing answers stage.